Dynamic hardness of wood - measurements with an automated portable hardness tester - Assis, Albert Augusto de [UNESP]; Alexandre, Rogerio Pinto [UNESP]; Ballarin, Adriano Wagner [UNESP] (Walter De Gruyter Gmbh, 2017)
A research group on forest products from School of Agriculture - Sao Paulo State University. Brazil developed a portable hardness tester for wood, which is based on a displacement transducer and an embedded electronic processor for dynamic evaluation of hardness. This paper presents the results of calibration tests of the equipment, carried out on seven species of Eucalyptus. A new methodology for dynamic hardness calculation has been introduced, which relays on the reaction force of the indentation, while the measurements of indentation depth are performed under load. A moderate to strong linear correlation to Janka hardness and its variations were found. This new approach avoids the classical problems of Brinell hardness test in terms of sinking- in (causing diffuse edges) and elastic recovery of the indentation.
Keywords: Brinell hardness; dynamic hardness; Janka hardness; portable equipment; wood